American Public Policy - PETERS, B. Guy (Franklin Watts, 1982)
Now in its eighth edition, B. Guy Peterss trusted text once again provides a meticulous overview of the process behindand the current state of American public policy. In addition to balanced and comprehensive coverage of governmental structures and policymaking procedures, Peters addresses an array of specific policy issues as well as cost-benefit and ethical analysis.